Glacial recession in Andean North‑Patagonia (Argentina): microbial communities in benthic biofilms of glacier‑fed streams - Vega, Evelyn (2023)
Global climate change produces impor- tant shifts in the glacial runoﬀ, modifying the relative contributions of meltwater and glacial clay discharges into headwater streams. Physical and chemical factors of glacier-fed streams are aﬀected, such as total suspended solids (TSS), and nutrient concentrations. Here, we analyze the composition of the bioﬁlm bacterial community by 16S rRNA sequencing along a glacier-fed network (Upper Río Manso) located in North Patagonian Andes (Argentina). We also anayzed changes in environmental factors in relation to the bacteria composition in diﬀerent seasons (spring, summer, and autumn). Our results showed that the dominant phyla were Proteobacteria, Cyanobacteria, Bacteroidota, Actinobacteriota, and Acidobacteriota. Bacterial community composition changes longitu-dinally and seasonally in relation to glacial inﬂuence (TSS and phosphorus concentrations). We identiﬁed phylotypes of Proteobacteria (Polaromonas, Rho- doferax, and Methylotenera) that were only present in headwaters of the ﬂuvial systems. In addition, Cyano-bacteria also presented substantial changes along the main course of Manso River and among seasons. The increase of Cyanobacteria abundance was favored by the glacial inﬂuence both longitudinally and season-ally. Overall our results contribute to the understand-ing of the patterns of biodiversity and bacterial com- position under a constant glacial retreat.